Socialization Of Clean And Healthy Living Behavior (PHBS) To Students At State Elementary School 02 Kabawetan, Suka Sari Village - Muhamad Ulga Alhusin; Alda Meisy Cantika; Inayah Aprilia Putri; Yustina Nadia Pandiangan; Hikmah Kasih; Liya Lugita Sari (Jurnal Inovasi Kerja Nyata, 2026)
Clean and Healthy Living Behavior (PHBS) is an essential strategy for improving public health, particularly among elementary school children (Ministry of Health RI, 2021). At this developmental stage, children are still forming daily habits and therefore require guidance to consistently practice personal hygiene. This educational activity was conducted at SDN 02 Kabawetan and involved 40 students from grades III and IV. The aim of the program was to enhance students’ knowledge and awareness regarding the importance of maintaining personal hygiene, especially in handwashing, dental hygiene, and nail cleanliness. The methods used included delivering material through PowerPoint presentations, animated videos, and live demonstrations, enabling students to better understand the concepts in an engaging manner. This PHBS education proved beneficial in increasing students’ understanding of disease prevention efforts, particularly in reducing the risks of diarrhea, dental caries, and helminth infections through clean and healthy behaviors. The results showed that students demonstrated a good understanding of the material, with approximately 80% able to explain the steps of PHBS and its health benefits. Overall, the activity had a positive impact on students’ health-related behaviors and is expected to be continuously implemented to establish long-term clean living habits and support a healthier school environment.